2003
DOI: 10.1182/blood-2002-06-1694
|View full text |Cite
|
Sign up to set email alerts
|

Human CD34+ hematopoietic stem cells capable of multilineage engrafting NOD/SCID mice express flt3: distinct flt3 and c-kit expression and response patterns on mouse and candidate human hematopoietic stem cells

Abstract: The cytokine tyrosine kinase receptors c-kit and flt3 are expressed and function in early mouse and human hematopoiesis. Through its ability to promote ex vivo expansion and oncoretroviral transduction of primitive human hematopoietic progenitors, the flt3 ligand (FL) has emerged as a key stimulator of candidate human hematopoietic stem cells (HSCs). However, recent studies in the mouse suggest that though it is present on shortterm repopulating cells, flt3 is not expressed on bone marrow long-term reconstitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 40 publications
3
72
0
2
Order By: Relevance
“…11,12 However, a recent study showed that in human CD34-positive cells, the FLT3-positive fraction has the active long-term reconstituting activity. 31 The accumulated data clearly point to FLT3 as an important receptor in early hematopoiesis.…”
Section: Flt3 Receptor and Ligandmentioning
confidence: 99%
“…11,12 However, a recent study showed that in human CD34-positive cells, the FLT3-positive fraction has the active long-term reconstituting activity. 31 The accumulated data clearly point to FLT3 as an important receptor in early hematopoiesis.…”
Section: Flt3 Receptor and Ligandmentioning
confidence: 99%
“…Around 40-80% of hCD34 þ bone marrow and cord blood cells express hFlt3 (Rappold et al, 1997;Sitnicka et al, 2003). Although a fraction of both the hFlt3 þ and the hFlt3 À populations gave rise to multilineage colonies containing all myelo-erythroid components, the hFlt3 þ hCD34 þ and hFlt3 À hCD34 þ populations predominantly formed GM and erythroid colonies, respectively (Rappold et al, 1997;Gotze et al, 1998;Sitnicka et al, 2003), and cells with NOD-SCID reconstitution activity reside in the hCD34 þ hFlt3 þ fraction (Sitnicka et al, 2003). Our recent experiments have revealed that hFlt3 is expressed in the entire human bone marrow and cord blood hCD34 þ hCD38 À population, and purified hFlt3 þ hCD34 þ hCD38 À cells could reconstitute multilineage cells for a long term in the NOD-SCID/ IL-2Rgnull xenogeneic transplantation system (unpublished data).…”
Section: And Hcd90mentioning
confidence: 99%
“…2,3 The receptor tyrosine kinase FLT3 is expressed in CD34 ϩ hematopoietic stem/progenitor cells and plays an important role in normal hematopoiesis. [4][5][6][7] FLT3 is also expressed on the leukemic blasts in the majority of cases of acute leukemia, although its expression is no longer tightly coupled to CD34 expression. [8][9][10][11] Internal tandem duplication mutations of FLT3 (FLT3/ITD mutations) occur in approximately 23% of patients with AML and are associated with an increased relapse rate and reduced overall survival.…”
Section: Introductionmentioning
confidence: 99%